A Rheme of One’s Own: How ‘Original’ do we Expect Students to be? - Johnson, A.; Clerehan, R. (Journal of University Teaching and Learning Practice, 2005)
Current discussions of plagiarism in the university havetaken something of a criminological turn. At the sametime, there is a tendency to focus on technologicalsolutions. Against these trends, we argue that plagiarismremains, fundamentally, a philosophical and pedagogicalissue for universities, related to understanding themeaning of originality and using sources for differentdisciplines.Toward this goal we place the notion of originality in itshistorical and disciplinary contexts, and question the viewthat it is a natural and universal quality of good writing.The practice of assessing undergraduate students ontheir ability to produce ‘original’ texts depends on a notionof originality that is unstable and uncertain. We examinea sample of statements about originality given to studentsand explore the nature of the demands placed on studentwriters in the internationalised university.